THE DEVELOPMENT OF METHOD FOR MINT AND TURMERIC ESSENTIAL OILS IDENTIFICATION AND QUANTITATIVE ANALYSIS IN COMPLEX DRUG - O. G. Smalyuh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of our study was to develop the method for identification and assay of essential oils of mint and turmeric in complex medicinal product in capsule form.